Advances on Bioactive Metabolites with Potential for the Biocontrol of Plant Pathogenic Bacteria - Pierluigi Reveglia; Gaetano Corso; Antonio Evidente (Pathogens)
The increase in the world population, which will be almost 10 billion by 2050, will require considerable efforts to significantly increase food production. Despite the considerable progress made in agriculture, this need is becoming an emergency due to desertification, environmental pollution and climate changes. Biotic stresses, such as pathogenic bacteria and fungi, primarily contribute to significant losses in agricultural productivity and compromise food safety. These harmful agents are predominantly managed using large quantities of synthetic pesticides. However, this widespread use has led to substantial environmental pollution, increased pest resistance and toxic residues in agricultural produce, which subsequently enter the food supply, posing severe health risks to humans and animals. These challenges have significantly driven the advancement of integrated pest management strategies to reduce or eliminate synthetic pesticides. A practical and viable alternative lies in biopesticides—methods developed from natural products that are safe for human and animal health. This approach aligns with the strong demand from consumers and public authorities for safer pest control solutions. This review was focused on the isolation, chemical and biological characterization of natural products for the biocontrol of phytopathogenic bacteria and, in some cases, fungi with potential eco-friendly applications.